Effect of hot water treatment in controlling fusarium wilt of gladiolus (Bangladesh Journal of Agricultural Research, 2017)
The experiment was conducted at the Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI), Gazipur during 2010-12 following two factors RCB design with four replications. The levels of Factor A (Duration): were i) T1 = 5 minutes, ii) T2 = 10 minutes and iii) T3 = 15 minutes. Factor B (Water temperature): i) A1 = 500C, ii) A2 = 520C, iii) A3 = 540C, iv) A4 = 560C and v) A5 = Control (normal water). The treatment combinations were evaluated against the wilt disease of gladiolus (Fusarium oxysporum f. sp. gladioli) under naturally infested field condition. Corm treated with hot water at 540C for 5 minutes was very effective in inhibiting the wilt disease incidence and thereby resulting better corm emergence, flower sticks plot-1, corm plot-1 and comel yield of gladiolus. Corm treated with hot water at 520C for 10 minutes appeared moderately effective against Fusarium wilt as well as better flower, corm and cormel yield of gladiolus under field condition.Bangladesh J. Agril. Res. 42(3): 393-401, September 2017